MR-gated intracranial CSF dynamics: evaluation of CSF pulsatile flow. - Njemanze, P C; Beck, O J (American Journal of Neuroradiology, 1989)
This article describes a new imaging method, called MR-gated intracranial CSF (liquor) dynamics, or MR-GILD. Pulsatile flow in CSF pathways is revealed by the difference between diastolic- and systolic-gated images. The images clearly demonstrate the ventricles, cisterns, and vascular structures. The dependence of CSF movement on arterial pulse transformation is analyzed, illustrative cases are given to show some pathologic variations, and the use of MR-GILD for neurosurgical patients is discussed.